Image fidelity improvement in digital holographic microscopy using optical phase conjugation. (January 2018) - Chan, Huang-Tian; Chew, Yang-Kun; Shiu, Min-Tzung; Chang, Chi-Ching
Highlights: Optically suppressing noise in the object arm prior to recording stage via phase conjugation technique. The technique employed has intrinsically improved the image fidelity of reconstructed images. Digital holography has been brought to a higher level on general purposes. Abstract: With respect to digital holography, techniques in suppressing noises derived from reference arm are maturely developed. However, techniques for the object counterpart are not being well developed. Optical phase conjugation technique was believed to be a promising method for this interest. A 0°-cut BaTiO3 photorefractive crystal was involved in self-pumped phase conjugation scheme, and was employed to in-line digital holographic microscopy, in both transmission-type and reflection-type configuration. On pure physical compensation basis, results revealed that the image fidelity was improved substantially with 2.9096 times decrease in noise level and 3.5486 times increase in the ability to discriminate noise on average, by suppressing the scattering noise prior to recording stage.